Seleção e caracterização molecular e fermentativa de leveduras personalizadas para a produção de vinhos brasileiros - Novaes, Hosana Ribeiro de (Universidade Federal de São Carlos, 2022)
Brazilian wine production has been standing out with high quality awarded wines around the world. However, major changes are still needed so that our country can compete with other wineries in the world. Among them, we can highlight the use of selected yeasts adapted to grapes planted in Brazilian soil. So that they can, in addition to metabolizing the sugars present in the grapes, produce primary and secondary metabolic compounds crucial for the elaboration of a typical premium quality wine. In the Brazilian market there are only commercial yeast strains acquired from international suppliers, due to Brazil does not have this resource. The use of these commercial yeasts in the winemaking process does not provide the wine with its own organoleptic characteristics, since these strains, because they are not selected on Brazilian soil, do not have the adapted metabolic pathways necessary to increase the typicality of local wines. Observing this scenario, the present project followed the dynamics of microorganisms during 3 harvests/production both in the vines and during the fermentation process, in a winery in the region of Amparo-SP, aiming at the selection of native yeasts to act as initiators (starters) in the fermentation process. A similar process was carried out on a laboratory scale in January 2019 using the must grape that was being vinified at the winery in order to compare both fermentation processes. Through this monitoring, we isolated 406 yeasts from both processes, being 347 non-Saccharomyces yeasts that, after sequencing the ITS region, we identified that they were distributed in 23 different species and 65 Saccharomyces. When performing genotyping analyzes on these isolated Saccharomyces strains, 5 they were shown to be different from each other and also different from the commercial strains commonly used for wine production in Brazil. Therefore, they are new isolated strains. The other strains showed the same amplification profile of the commercial strains and the 5 new identified strains. The analyses also verified that the isolated Saccharomyces strains isolated in the winery environment actively participated in the fermentation process. These new strains were submitted to physiological analyzes to verify their capacity and performance in wine production. In all analyzes realized, they showed performance equal to or superior to that of commercial strains. These strains would already be naturally more adapted to the fermentation process and could bring peculiar characteristics to the production of wines, contributing to the elaboration of a distinct drink. In addition, an understanding of the yeast microbiota present both in the winery and in the fermentation process can help to better understand the succession dynamics of these microorganisms, being an important element in the characterization of the national wine’s terroir, thus preserving its historical identity, quality and geographical origin.
Selection and molecular and fermentative characterization of customized yeasts for the production of Brazilian wines
Keywords: Leveduras; Terroir; Vitivinícola; Saccharomyces cerevisiae; Fermentação; Terrassos; Vinho; Yeast; Winery; Fermentation; Wine; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS